2020
DOI: 10.3390/s20102784
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Copper-Less Gas Electron Multiplier Detectors Responses to Soft X-rays

Abstract: In this paper, we report on the systematic study of different variants of X-ray detectors based on Gas Electron Multiplier (GEM) technology using modified GEM foils with greatly reduced amount of copper. The main goal of this study was understanding the performance of such detectors applied in X-Ray Fluorescence (XRF) elemental analysis. Reduction of the amount of copper in the detector structure is crucial for suppression of XRF background from copper, but one has to ensure that key detector parameters are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Such a relatively simple modification results in a very significant reduction in the Cu fluorescence background, by a factor of 7 for the Ar/CO (70/30) gas mixture [ 31 ]. The results of detailed studies of such copperless detectors have been reported elsewhere [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Such a relatively simple modification results in a very significant reduction in the Cu fluorescence background, by a factor of 7 for the Ar/CO (70/30) gas mixture [ 31 ]. The results of detailed studies of such copperless detectors have been reported elsewhere [ 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Micropattern gas detectors (MPGDs) are charged particle-tracking detectors for particle physics research which provide ∼50 µm resolution while tolerating very intense beams such as in cancer therapy applications. 8 This technology is being explored for beam diagnostics as well as protoncomputed tomography. Finally, artificial intelligence (AI) techniques under exploration for particle physics detector design and optimization clearly can be leveraged for improving patient care via medical imaging and adaptive planning development.…”
Section: Crystals Cameras and Detectorsmentioning
confidence: 99%
“…Imaging approaches here target positron‐emitting radionuclides produced by hadron irradiation or using gamma cameras or Compton cameras designed to detect beam‐induced prompt gamma rays. Micropattern gas detectors (MPGDs) are charged particle‐tracking detectors for particle physics research which provide ∼50 μm resolution while tolerating very intense beams such as in cancer therapy applications 8 . This technology is being explored for beam diagnostics as well as proton‐computed tomography.…”
Section: Summary Of the Initial Workhop Of 2021mentioning
confidence: 99%
“…One of the approaches is to remove most of the copper conductive layer and to use only the chromium layer that is used to improve the adhesion between the kapton and the copper layer to bias the GEM foil [73]. Despite the clear contamination suppression reported [74], the process in which these GEM foils are produced is not clear and the chromium may also produce a contamination, with lower intensity, in the region of interest, at 5.41 keV [59].…”
Section: Copper Contamination Of the Energy Spectramentioning
confidence: 99%